2009
DOI: 10.1152/ajpregu.00179.2009
|View full text |Cite
|
Sign up to set email alerts
|

CaMKK is an upstream signal of AMP-activated protein kinase in regulation of substrate metabolism in contracting skeletal muscle

Abstract: Multiple signals have been shown to be involved in regulation of fatty acid (FA) and glucose metabolism in contracting skeletal muscle. This study aimed to determine whether a Ca(2+)-stimulated kinase, CaMKK, is involved in regulation of contraction-induced substrate metabolism and whether it does so in an AMP-activated protein kinase (AMPK)-dependent manner. Rat hindlimbs were perfused at rest (n = 16), with 3 mM caffeine (n = 15), with 2 mM 5-aminoimidazole-4-carboxamide 1-beta-d-ribofuranoside (AICAR; n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
103
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 58 publications
13
103
1
3
Order By: Relevance
“…Indeed, we have shown that when CaMKII or CaMKK was inhibited during caffeine stimulation, there were subsequent decreases in AMPKā£ 2 activity along with decreases in the rates of FA uptake, glucose uptake, and FA oxidation (1,35). In line with these previous results, we measured an increase in AMPKā£ 2 activity in caffeine-treated WT mice in this study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Indeed, we have shown that when CaMKII or CaMKK was inhibited during caffeine stimulation, there were subsequent decreases in AMPKā£ 2 activity along with decreases in the rates of FA uptake, glucose uptake, and FA oxidation (1,35). In line with these previous results, we measured an increase in AMPKā£ 2 activity in caffeine-treated WT mice in this study.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown by us and others that caffeine-induced increases in Ca 2Ļ© signaling regulate substrate metabolism, possibly via AMPK activation (1,6,22,35). Indeed, we have shown that when CaMKII or CaMKK was inhibited during caffeine stimulation, there were subsequent decreases in AMPKā£ 2 activity along with decreases in the rates of FA uptake, glucose uptake, and FA oxidation (1,35).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Based on the fi ndings from studies using muscle contractions and/or pharmacological approaches, it has been suggested that AMPK could be a major regulator of contraction-induced FAT/CD36 translocation in skeletal muscle ( 11,17 ). In the present skeletal muscle and heart muscle ( 17,18,36,37 ). During muscle contractions, FAT/CD36 translocation to the plasma membrane has been shown in rat gastrocnemius muscle ( 17,18 ), and the increase of FAT/CD36 in the plasma membrane has been associated with an increase in Fig.…”
Section: Effect Of Contraction Time On Cellular Signaling In the Perfmentioning
confidence: 87%